URGENSI TEORI KOGNITIVISME DAN IMPLEMENTASINYA DALAM PEMBELAJARAN PAI DI UPT SD NEGERI 358 GRESIK - Aisyah, Sitti; Rohmani, Abd. Hadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to examine the urgency and implementation of cognitive theory in the learning process of Islamic Religious Education (PAI) at UPT SD Negeri 358 Gresik. Cognitive theory emphasizes mental processes in which students actively construct knowledge through interaction with their environment and personal experiences. A qualitative research approach was applied, using interviews, observations, and documentation as data collection techniques. The findings indicate that the application of cognitive theory in this school is realized through several instructional strategies, including the setting of clear learning goals, the use of positive reinforcement, repeated practice, the development of metacognitive skills, and the structured organization of learning materials. These approaches have been effective in enhancing students’ motivation, active participation, and conceptual understanding of PAI content. However, several challenges were identified, such as low student motivation, limited learning facilities, and insufficient instructional time. Therefore, institutional support, teacher training, and innovative teaching strategies are essential to ensure the optimal application of cognitive theory. The study highlights the significance of adopting a cognitive approach to create meaningful, contextual, and character-oriented PAI learning experiences. ABSTRAKPenelitian ini bertujuan untuk menganalisis urgensi dan implementasi teori kognitivisme dalam pembelajaran Pendidikan Agama Islam (PAI) di UPT SD Negeri 358 Gresik. Teori kognitivisme menekankan proses mental dalam pembelajaran, di mana siswa secara aktif membangun pengetahuan melalui interaksi dengan lingkungan dan pengalaman hidup mereka. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi teori kognitivisme di sekolah ini diwujudkan melalui strategi pembelajaran seperti penetapan tujuan yang jelas, penggunaan penguatan positif, latihan berulang, pengembangan keterampilan metakognitif, serta penyusunan materi secara sistematis. Strategi ini terbukti meningkatkan motivasi, partisipasi aktif, dan pemahaman konseptual siswa terhadap materi PAI. Namun, terdapat beberapa kendala seperti rendahnya motivasi siswa, keterbatasan fasilitas, serta waktu pembelajaran yang terbatas. Oleh karena itu, diperlukan dukungan kelembagaan, pelatihan guru, serta inovasi dalam strategi pembelajaran agar teori kognitivisme dapat diimplementasikan secara optimal. Temuan ini menegaskan pentingnya pendekatan kognitivisme dalam menciptakan pembelajaran PAI yang bermakna, kontekstual, dan berorientasi pada pengembangan karakter.